2015
DOI: 10.1166/jnn.2015.9177
|View full text |Cite
|
Sign up to set email alerts
|

Poly(L-lactide) Nanoparticles Reduce Amphotericin B Cytotoxicity and Maintain Its <I>In Vitro</I> Antifungal Activity

Abstract: In this study, poly(L-lactide) (PLA) nanoparticles containing amphotericin B (AmB) were developed, and the in vitro cytotoxicity to human erythrocytes and efficacy on strains of Candida spp. were evaluated. The nanoparticles were prepared using an emulsion/solvent evaporation method and were characterized with respect to size, size distribution, AmB encapsulation efficiency, AmB state of aggregation, and AmB in vitro release profile. The mean particle size was 225 nm, and the AmB encapsulation efficiency was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…[28][29][30] First, 10 mg of AmB and 100 mg of MPP triblock copolymer were co-dissolved in 200 mL methanol with the help of ultrasound. The methanol was recovered by evaporating at 55°C under reduced pressure (RE-52A; Shanghai Ya Rong Biochemistry Instrument Factory, Shanghai, China) to form a uniform thin film.…”
Section: Preparation Of Amb/mpp Micellesmentioning
confidence: 99%
“…[28][29][30] First, 10 mg of AmB and 100 mg of MPP triblock copolymer were co-dissolved in 200 mL methanol with the help of ultrasound. The methanol was recovered by evaporating at 55°C under reduced pressure (RE-52A; Shanghai Ya Rong Biochemistry Instrument Factory, Shanghai, China) to form a uniform thin film.…”
Section: Preparation Of Amb/mpp Micellesmentioning
confidence: 99%
“…Similar results from Tang et al [51] indicate increased fungicidal activity of amphotericin B after incorporation into polymeric nanoparticles. It was also shown that encapsulation of amphotericin B poly(L-lactide) (PLA) nanoparticles reduces hemolytic activity of the drug without affecting its antifungal properties [10]. Moreover, a study from 2013 reported that amphotericin B-encapsulated PLGA-DMSA (poly[lactic-co-glycolic] acid and dimercaptosuccinic acid) nanoparticles might be an effective delivery system for the treatment of cutaneous leishmaniasis [52].…”
Section: Recent Advances In Application Of Antibioticconjugated Nanopmentioning
confidence: 99%
“…Specifically, nanosystems offer antibiotic delivery to the site of infection and extension of its action due to controlled release [7]. Additionally, the use of nanotechnology provides important improvements in the pharmacokinetics of antibiotics whose application is limited due to low solubility, poor bioavailability after oral administration, short half-life, high toxicity or instability in physiological conditions ( Figure 1) [8][9][10]. A broad spectrum of antimicrobial activity described for a variety of nanomaterials supports the idea that the employment of antibiotic-conjugated nanoformulations will provide a more efficient way to overcome the ever-growing drug resistance of pathogens [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The samples were analyzed by HPLC (Waters 2695 Alliance HPLC system, Milford, MA). The mobile phase consisted of acetonitrile, methanol and water mixture (40:50:10, v/v/v) at a flow rate of 1 mL/min, in an isocratic mode 28 . The injection volume was 20 mL and photodiode array detector was operated at 408 nm.…”
Section: Determination Of Amb Encapsulation Efficiencymentioning
confidence: 99%